Towards a Better Understanding on the Relationship between Knowledge Sharing and Public Service Motivation (Journal of Governance and Development (JGD), 2020)
Knowledge sharing has been acknowledged as the right mechanism for public servants to share best practices in performing work among workers. The sharing of best practices on learning by actions (doing) seems to enhance motivation among public servants to provide quality services. Thus, the purpose of this study is to examine the relationship between knowledge sharing and public service motivation among civil servants in the Department of Student Affairs, UiTM Merlimau and Public Works Department (JKR), Jasin, Malaysia. A total of 150 questionnaires were distributed but only 118 questionnaires were validly returned and used. The findings demonstrate that the level of knowledge sharing practices in both organisations is at moderate level. Pearson correlation analysis shows that policy making, commitment to public interests, social justice, civic duty, compassion and self-sacrifice have significant relationships with knowledge sharing practices. Meanwhile, multiple regression analysis reveals that only commitment to public interests, social justice as well as civic duty significantly influence the practices of knowledge sharing. The findings conclude that knowledge sharing is key element used by civil servants in producing public service motivation.